Blood Cells Depletion after Chemotherapy in Iraqi Women with Breast Cancer - Reem M. Obaid 1, Farah Tareq Yaseen2 , Mahmood Yaseen Mukhlif 3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The research was aimed to study the effect of chemotherapy on white blood cells especially lymphocytes,and the relationship between chemotherapy and red blood cells, platelets in women with breast cancer. Ourresults showed that the mean ± SE of White Blood Cells (WBCs) and lymphocytes before treatment wassignificantly higher than the mean ± SE of lymphocytes and WBCs after treatment at (P<0. 01), the mean± SE of Red Blood Cells (RBCs) and platelets before treatment was higher than the mean ± SE of RBCsand lymphocyte after treatment at (P<0. 01). The reason probably due to the poor nutrition and the effect ofcancer of the breast on erythropoiesis on the cases, or metastasis to the bone marrow from breast cancer canbe associated with suppression of blood cells synthesis. We concluded that chemotherapy for breast canceris in association with long-term changing in immune system parameters and other cells during clinicalmanagement.